Acceleration the Liver Regeneration by Hyperbaric Oxygen Therapy in Model Rabbit - Zainab J. Malik (Journal of Global Pharma Technology, 2018)
In this study, we were investigating the importance of therapy of the hyperbaric oxygenon the regeneration of liver. Sixteen mature rabbits of Iraqi breed were used. The animals divided equally into two groups (control and treated). The anesthetizing of animals was done byatropine sulphate (1mg /Kg B.W) intramuscularly; as premedication and 15 minutes later a mixture of xylazine hydrochloride (20mg /Kg B.W) and Ketamine hydrochloride (40 mg /Kg B.W) are giving intramuscularly. In control group the rabbits were anesthetized and preparation the site of operation was done in the upper part of abdomen. Surgical incision made and exposure of fourth lobe of the live. The liver handling by thump forceps and the stitches was done on the lobe. Three knots were tied and we used dissecting scissors in order to cut the tied lobe just distal to the suture. After that the wall of abdomen was re approximated with a running 3-0 Polyglactinsuture, then the skin closed with a running 2-0 polyamide suture. While in treated group the same procedure that mentioned above with hyperbaric oxygen therapy was done. The clinical parameters included temperature, respiratory, and heart rates, were within acceptable limits post operatively in all animals in two groups. The intra-abdominal adhesions in different degrees of evaluations and occurred among liver, different organs and abdominal wall that more frequency in control group when compared with treated group. Histopathological Examinations was done by taken the liver biopsies on 15rd, and 30th, day postoperatively. The histopathological results of this study revealed that the liver regeneration more maturity in treated group than in control group.Keywords: Hyperbaric oxygen therapy, Liver, Rabbit, Regeneration.